Individualized Homeopathic Medicines as Adjunctive Treatment of Pediatric Epilepsy: A Double-Blind, Randomized, Placebo-Controlled Trial - Gupta, Bharti; Misra, Pankhuri; Karuppusamy, Avaranjika; Balamurugan, Dharshna; Parewa, Maneet; Tomar, Maneela; Rai, Shruti; Vashishth, Himani; Sadhukhan, Satarupa; Singh, Navin Kumar; Koley, Munmun; Saha, Subhranil (Homeopathy, 2022)
Introduction Epilepsy, one of the most common neurological diseases, contributes to 0.5% of the total disease burden. The burden is highest in sub-Saharan Africa, central Asia, central and Andean Latin America, and south-east Asia. Asian countries report an overall prevalence of 6/1,000 and that in India of 5.59/1,000. We examined whether individualized homeopathic medicines (IHMs) can produce a significantly different effect from placebos in treatment of pediatric epilepsy in the context of ongoing standard care (SC) using anti-epileptic drugs (AEDs).Methods The study was a 6-month, double-blind, randomized, placebo-controlled trial (n = 60) conducted at the pediatric outpatient department of a homeopathic hospital in West Bengal, India. Patients were randomized to receive either IHMs plus SC (n = 30) or identical-looking placebos plus SC (n = 30). The primary outcome measure was the Hague Seizure Severity Scale (HASS); secondary outcomes were the Quality of Life in Childhood Epilepsy (QOLCE-16) and the Pediatric Quality of Life inventory (PedsQL) questionnaires; all were measured at baseline and after the 3rd and 6th month of intervention. The intention-to-treat sample was analyzed to detect group differences and effect sizes.Results Recruitment and retention rates were 65.2% and 91.7% respectively. Although improvements were greater in the IHMs group than with placebos, with small to medium effect sizes, the inter-group differences were statistically non-significant – for HASS (F1, 58 = 0.000, p = 1.000, two-way repeated measures analysis of variance), QOLCE-16 (F1, 58 = 1.428, p = 0.237), PedsQL (2–4 years) (F1, 8 = 0.685, p = 0.432) and PedsQL (5–18 years) (F1, 47 = 0.000, p = 0.995). Calcarea carbonica, Ignatia amara, Natrum muriaticum and Phosphorus were the most frequently prescribed medicines. No serious adverse events were reported from either of the two groups.Conclusion Improvements in the outcome measures were statistically non-significantly greater in the IHMs group than in the placebos group, with small effect sizes. A different trial design and prescribing approach might work better in future trials.Trial registration CTRI/2018/10/016027
Keywords: homeopathy; pediatric epilepsy; placebo; quality of life; randomized controlled trial; seizure